Prolonged Use of Protective Masks Induced Facial Skin Injury in Primary Healthcare Workers during COVID-19 Pandemic: A Systematic Review - Yapanto, Alvian Mohamad; Isnaeni, Aulia Rahma; Lestari, Khairani Ayu; Satyarsa, Agung Bagus Sista (Institute of Topical Disease Universitas Airlangga, 2022)
COVID-19 transmission necessitates health workers to use personal protective equipment (PPE), especially protective masks when delivering medical services. Long-term use of protective masks might cause facial skin injuries. Our study aims to provide a systematic review to explore the phenomenon and incidence of protective masks induced facial skin injuries in primary healthcare workers. This systematic review was created by obtaining articles from the PubMed database and the Cochrane library from 2020 to 2021, using the keywords